1971
DOI: 10.1080/1355800710080102
|View full text |Cite
|
Sign up to set email alerts
|

A Selective Survey of Microteaching

Abstract: The term " microteaching" has been quoted in a variety of contexts, but is most often applied to the use of closed circuit television to give immediate feedback of a trainee teacher's performance in a simplified environment. Among advantages claimed are the controlled and structured nature of the format, an economy of time and effort and an improved research and evaluation facility. There is evidence that microteaching produces measurable changes in teacher behaviour, and that beneficial results can be obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1972
1972
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…A teacher is therefore a person whose job is to teach, especially in a school. (Mcaleese & Unwin, 1971;Otsupius, 2014). As before mentioned, students had asked to draw up a lesson plan and the lecturer will provide input before teaching online on a predetermined day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A teacher is therefore a person whose job is to teach, especially in a school. (Mcaleese & Unwin, 1971;Otsupius, 2014). As before mentioned, students had asked to draw up a lesson plan and the lecturer will provide input before teaching online on a predetermined day.…”
Section: Discussionmentioning
confidence: 99%
“…The microteaching method has benefited in many countries in training teachers. Several studies have shown that microteaching is a viable means to fulfill the desired goals in preparing teacher candidates to become effective and reflective teachers (He & Yan, 2011;Koross, 2016;Mcaleese & Unwin, 1971). Another previous research showed that the activity of microteaching can provide a window into students' reflective processes (I'Anson et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Laughlin and Moulton (1975) define micro teaching as a method of performance training which is designed to isolate teaching process components, so the the trainee can master how to teach in various teaching environment. Additionally, McAleese, W. R., & Unwin, D. (1971) define the learning of micro teaching as a situation of learning applied within certain limited number of students and hours, namely between five to 20 minutes with three to ten students. Similarly, Loewenberg Ball, D., & Forzani, F. M. (2009) delineate that micro teaching is one of the teaching practices in micro format to form and develop the teaching skills.…”
Section: Micro Teachingmentioning
confidence: 99%
“…So given the variety of possible conceptualisations of the supervisor's role and the paucity of empirical evidence on differential effectiveness in achieving various outcomes, it appears necessary to rely upon an eclectic listing of possible and overlapping supervisor tasks. McAleese and Unwin (1971) have surveyed some of the early attempts to delineate aspects of supervisory role, including perceptions of the supervisor as: a resource for information on curriculum and methods, an adviser on approaches to the reteach lesson, an interpreter of pupil feedback, an evaluator of performance,…”
Section: Definition Of the Supervisor's Rolementioning
confidence: 99%